Penerapan Sistem Prediksi Perekrutan Karyawan Menggunakan Metode Naive Bayes - Dwi Agustina; Umi Chotijah (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2025)
Recruitment at CV Gemika is a strategic process aimed at attracting, selecting, and retaining the best talent to support the company's vision and mission. Through a systematic approach, CV Gemika implements recruitment methods that focus on the specific needs of each position while creating a positive experience for candidates. This process includes determining criteria, utilizing various recruitment channels, and applying effective interview techniques. Additionally, CV Gemika emphasizes the importance of diversity and inclusion within the team to enhance innovation and performance. Thus, recruitment at CV Gemika serves not only to fill positions but also to build a strong and sustainable organizational culture.